Pragmatic Analysis in Speech Acts (bahasa ogan) used between Buyers and Wanita Bakul in Batu putih Village - Shofiyatul Huriyah; Emilia Contessa; Nurhasanah; Henny Yulia (Journal of Pragmatics Research, 2024)
This research aims to discover the types of locutionary, illocutionary, and perlocutionary speech acts used by buyers and Wanita Bakul in Batuputih village. The method used in this research is qualitative with descriptive type. The data collection techniques used are recording techniques and listening and recording techniques. The data source in this research was obtained from buyers and Wanita Bakul in Batuputih village, who engaged in speech act interactions using oganese language in buying and selling transactions. The researchers used proficient free involved listening, recording, and Wanita Bakul note-taking techniques to collect the data required in this research. The results show that the speech acts used in buying and selling interactions in  Batuputih village, total number of speech acts was 84, locutionary act 9, illocutionary act 25 and perlocutionary act 29. The perlocutionary act is the most dominant speech act between buyers and Wanita Bakul interactions in Batuputih village.